2017
DOI: 10.1002/ajmg.a.38121
|View full text |Cite
|
Sign up to set email alerts
|

KBG syndrome: An Australian experience

Abstract: In 2011, heterozygous mutations in the ANKRD11 gene were identified in patients with KBG syndrome. Since then, 100 cases have been described with the expansion of the clinical phenotype. Here we present 18 KBG affected individuals from 13 unrelated families, 16 with pathogenic mutations in the ANKRD11 gene. Consistent features included intellectual disability, macrodontia, and the characteristic broad forehead with hypertelorism, and a prominent nasal bridge. Common features included hand anomalies, cryptorchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 13 publications
5
35
0
Order By: Relevance
“…No patients had a recognized diagnosis of autism spectrum disorder. Reports of this disorder in KBG are heterogeneous; it was reported to be as high as 47% by some authors , but much lower by others [Murray et al, 2017]. This difference may be due to varying ascertainment practices and referrals in different countries; such variability has already been noted for other conditions [Schneider et al, 2014].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…No patients had a recognized diagnosis of autism spectrum disorder. Reports of this disorder in KBG are heterogeneous; it was reported to be as high as 47% by some authors , but much lower by others [Murray et al, 2017]. This difference may be due to varying ascertainment practices and referrals in different countries; such variability has already been noted for other conditions [Schneider et al, 2014].…”
Section: Discussionmentioning
confidence: 91%
“…Eight major criteria were initially defined (macrodontia of the upper central permanent incisors, characteristic facial appearance, hand anomalies, neurological involvement, delayed bone age, costovertebral anomalies, short stature, and the presence of a first-degree relative with KBG syndrome) [Skjei et al, 2007]. Later on, delayed bone age and costovertebral anomalies were suggested to be removed, and macrodontia was not considered a mandatory criterion any longer Low et al, 2016;Murray et al, 2017]. Minor features that can further help to establish a clinical diagnosis are otitis media and hearing impairment, seizures, cryptorchidism, feeding problems, palatal insufficiency, and delayed anterior fontanelle closure [Low et al, 2016].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A distinctive neurocognitive and behavioral profile has been delineated (Lo‐Castro et al, ). Herrmann, Pallister, Tiddy, and Opitz () first described this disorder, whose clinical phenotype has been expanded by subsequent studies (Brancati et al, ; Brancati, Sarkozy, & Dallapiccola, ; Goldenberg et al, ; Kleyner et al, ; Low et al, ; Murray et al, ; Ockeloen et al, ; Parenti et al, ; Reynaert et al, ; Zollino et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although large series of patients with various variants in ANKRD11 gene have been reported worldwide (Goldenberg et al, ; Low et al, ; Murray et al, ; Ockeloen et al, ), it has not been reported in Egyptian patients before. Here we report two unrelated patients with special emphasis on the orodental findings.…”
Section: Introductionmentioning
confidence: 99%